A New Proposal for Severity Evaluation of Menière's Disease by Using the Evidence From a Comprehensive Battery of Auditory and Vestibular Tests - Huang, Shujian; Zhou, Huiqun; Zhou, Enhui; Zhang, Jiajia; Feng, Yanmei; Yu, Dongzhen; Shi, Haibo; Wang, Jian; Wang, Hui; Yin, Shankai (Frontiers in Neurology, 2020)
To date, no widely accepted criteria exists to quantify the severity of Menière’s disease using vestibular tests. This study aimed to compare association of hearing loss and vertigo severity with association of accurate assessments of vestibular function and the vertigo severity. The severity of vertigo was documented by a comprehensive medical history with number of vertigo attacks in the past 6 months and a Dizziness Handicap Inventory (DHI) questionnaire. The involvement of vestibular organs was verified by audio-vestibular tests in eighty definite MD patients. Correlations between DHI scores, number of vertigo attacks in the past 6 months, audio-vestibular function, and the number of involved vestibular end organs were evaluated. We show that there are no significant differences in either severity of vertigo or laboratory results across the degree of hearing loss. Furthermore, the number of involved vestibular end organs was significantly correlated with vestibulo-ocular reflex gain in anterior and posterior canal vHIT, interaural asymmetry ratio in VEMPs, as well as number of vertigo attacks in the past 6 months and DHI score. The vestibulo-ocular reflex gain in RCT was significantly correlated with the DHI Physical scores and number of involved vestibular end organs at 0.08 Hz. These results indicate that hearing loss is a poor indicator of vertigo severity in MD whereas the number of involved vestibular end organs may serve as an objective measure for MD progress. A battery of vestibular tests targeting different sensor organs is a complementary method for evaluating inner ear deficits and may aid in ‘grading’ the severity of MD.